The Transformation of a Turkish Islamic Movement: From Identity Politics to Policy (American Journal of Islam and Society, 2005)
Some scholars, such as Graham Fuller, tend to read the current experimentin Turkey as the successful political integration of an Islamic movementinto a democracy.1 Several facts support such an interpretation. Althoughthe JDP [Justice and Democracy Party] leadership denies its Islamic backgroundand claims to be a conservative democratic party, nonetheless, theparty did emerge out of the ashes of the Welfare [Refah] and the Virtue[Fazilet] parties that were closed down by the constitutional court oncharges of being a forum for and proponent of anti-secular activities.2Moreover, the majority of JDP’s deputies are observant Muslims in theirdaily lives. For instance, their spouses continue to wear headscarves, whichare banned in public offices, state ceremonies, and universities becausethey are regarded as a threat to Turkey’s secular character. The religiousobservance of JDP’s members poses several questions. Is the JDP an Islamicparty? Is it possible for an ex-Islamic movement to become a-Islamic or un-Islamic? Is the commitment of the JDP’s members to religious values intheir personal life sufficient to label the party Islamic? When does a movementor a party become or cease to be Islamic? Even if the party’s administrationdenies any connection with political Islam, can we still consider theparty to be Islamic?Alternatively, one may argue that JDP’s denial of being an Islamicparty is simply a compromise between the state and the JDP. The party, asthe argument goes, is free to govern the country as long as it stays withinTurkey’s strictly proscribed constitutional framework and ignores many ofits conservative constituency’s religious demands. This alternative interpretationfurther complicates the issue and raises following question: Is theJDP, rather than being the success story of an Islamic movement that hasadapted to a democratic and secular environment, an example of the ...